2019
DOI: 10.1080/24704067.2019.1566757
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of the Olympic Games: A Review

Abstract: Much has been written about the legacies of Olympic Games but there have been little efforts to synthesize current knowledge. This has led to inconsistencies in defining, contextualising and measuring these legacies. The literature review described in this paper provides an overview over research on the legacy of the Olympic Games from 1908 to 2016 that was published in peer-reviewed journals between 1984 and 2017.The analysis reveals a significant increase of literature dealing with Olympic legacy since 2008.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 76 publications
1
40
0
Order By: Relevance
“…First, as pointed out by Thomson et al (2019), legacy analysis has been done within a relatively short timeframe around the actual events. In their mapping of legacy literature, Bocarro, Byers, and Carter (2018) found that timeframes used to capture legacy rarely exceeded five years, which is in line with Scheu et al (2019), who found in their review that the average time of post-Games data collection was two years after the event. Given that it takes 15-30 years to gain insight into the true legacy of an event (Gratton & Preuss, 2008;Parent & Smith-Swan, 2013), neither the 2010 FIFA World Cup in South Africa nor the 2012 Olympic Games in London (two events that have dominated the legacy literature) are suitable for retrospective studies.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…First, as pointed out by Thomson et al (2019), legacy analysis has been done within a relatively short timeframe around the actual events. In their mapping of legacy literature, Bocarro, Byers, and Carter (2018) found that timeframes used to capture legacy rarely exceeded five years, which is in line with Scheu et al (2019), who found in their review that the average time of post-Games data collection was two years after the event. Given that it takes 15-30 years to gain insight into the true legacy of an event (Gratton & Preuss, 2008;Parent & Smith-Swan, 2013), neither the 2010 FIFA World Cup in South Africa nor the 2012 Olympic Games in London (two events that have dominated the legacy literature) are suitable for retrospective studies.…”
Section: Introductionsupporting
confidence: 56%
“…3 the following, we narrow the review to facilities. While some longitudinal studies of facilities exist, a majority of the papers are commentary (Scheu et al, 2019). In this section, we will look at events that were held from 1988 to 2006, a period in which actual legacy is possible to assess.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations